2010
DOI: 10.1002/jmri.22199
|View full text |Cite
|
Sign up to set email alerts
|

Improved pseudo‐continuous arterial spin labeling for mapping brain perfusion

Abstract: Purpose To investigate arterial spin labeling (ASL) methods for improved brain perfusion mapping. Previously, Pseudo-continuous arterial spin labeling (pCASL) was developed to overcome limitations inherent with conventional continuous arterial spin labeling (CASL), but the control scan (null pulse) in the original method for pCASL perturbs the equilibrium magnetization, diminishing the ASL signal. Here, a new modification of pCASL, termed mpCASL is reported, in which the perturbation caused by the null pulse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…The whole-brain 3D PCASL used in this study has several advantages: (1) whole brain coverage, (2) improved signal-to-noise ratio (SNR) in CBF, (3) reduced image distortion [9,10]. Previous studies have shown that PCASL has higher reliability than PASL and CASL [11].…”
Section: Discussionmentioning
confidence: 97%
“…The whole-brain 3D PCASL used in this study has several advantages: (1) whole brain coverage, (2) improved signal-to-noise ratio (SNR) in CBF, (3) reduced image distortion [9,10]. Previous studies have shown that PCASL has higher reliability than PASL and CASL [11].…”
Section: Discussionmentioning
confidence: 97%
“…Although pseudo‐continuous ASL techniques have been proposed that show great promise with respect to high labeling efficiency and SNR (19–21), FAIR ASST, with lower specific absorption rate (SAR), higher temporal resolution, and inherent immunity to off‐resonance effects, can still be a valuable alternative. Further studies comparing FAIR ASST with these or other ASL methods are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Luh et al demonstrated for balanced pCASL on humans at 7 T, that varying the phase during a prescan to measure the optimal phase increment was a robust way to improve the overall perfusion signal while keeping the imaging plane close to the isocenter. Moreover, other studies showed that correcting the control condition separately improves the ASL signal . However, the latter control correction strategies resulted in applying different frequencies for the label and the control conditions, leading to residual magnetization‐transfer effects.…”
Section: Introductionmentioning
confidence: 99%